PATENT CANCELLATION AS AN EFFORT TO PROTECT PATENTS REGISTERED IN INTELLECTUAL PROPERTY RIGHTS - Teuku Daudsyah; Muhammad Ridwan Lubis (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
Patents give the owner exclusive rights in an effort to prevent or stop other parties from making, using, offering for sale, selling or importing a product or a process, based on a patented invention, without the permission of the patent owner. Patents are a "powerful business tool" for companies to gain exclusivity rights to new products or processes, establish strong market positions and generate additional revenue through licensing. A product that is complex (such as a camera, mobile phone, or a car) combines a number of inventions which include several patents, which may be owned by different patent holders, but these patents can be canceled by several things, one of which is if there is no the novelty value of the idea that was initiated.